Effect of treatment with carnosin on cataract development in experimental ocular hypertension - I.N. Mikheitseva; Moutasim Waleed A.R. Aldahdooh; S.G. Kolomiichuk; Iu.A. Zhuravok (Ukrainian Society of Ophthalmologists, 2024)
Background: Senile cataract and glaucoma are the major age-related and degenerative ocular disorders that can cause loss of vision and blindness. To date, the question of the possible mechanisms involved in the impact of the glaucomatous process on the lens is still open. Purpose: To investigate the effect and mechanism of action of carnosine on the light-induced cataract model in the presence of experimental ocular hypertension (OHP). Materials and Methods: Rabbits were exposed to light from mercury arc-discharge lamps (type DRF-1000, 1000 W; bandpass range, 350-1150 nm) for 9 hours a day during a 10-week period to investigate the effect of regularly instilled (twice daily during the same period) carnosine on the development of opacities and thiol levels in the lens in the light-induced rabbit cataract model. OHP was induced bilaterally by injecting 0.1 mL of 0.3% carbomer solution into the anterior chamber of both eyes. Results: Mild changes in lens clarity (grades 1 to 3) were more common in rabbits treated with carnosine, whereas more apparent changes in lens clarity were more common in untreated animals. At 10 weeks, grade 5 lens opacity was noted in 8.3% of the rabbits treated with carnosine and in 20.3% of the untreated animals. Introduction of carnosine in the rabbit model of light-induced cataract in the presence of OHP resulted in 49.2% increase in the reduced glutathione levels, 28.3% decrease in oxidized glutathione levels, 40.7% increase in the sulfhydryl (thiol) levels and 28% decrease in the disulphide levels in the lenses of treated experimental animals compared to untreated experimental animals. Conclusion: A long-term intraocular treatment with carnosine in the rabbit cataract model (a) improved the resistance of the lens to cataractogenic phototoxicity in the presence of ocular hypertension and (b) contributed to substantial normalization of thiol levels in the lens, thus preventing oxidative damage to proteins.